Withholding of Original Certificates in Employment Agreements In terms of Human Rights - Alvin Berry Dika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aims of this study is to find out Withholding of Original certificates in Employment Agreements In terms of human rights. This study use research is normative legal research. Based on the descriptions in the chapters above, it can be concluded as follows:a.The detention of diplomas by companies against workers in work agreements/contracts is a violation of human rights because the act of detaining the original certificates prevents other people from finding better jobs and improving their standard of living.b.The legal consequences of holding a diploma are contained in Article 42 of the Regional Regulation of the Province of East Java Number 8 of 2016 with the threat of imprisonment for a maximum of 6 (six) months or a fine of a maximum of Rp. 50,000,000.00 (fifty million rupiah) but has no legal force binding nationally.